Gilbert's syndrome: clinical features, diagnostics, differential diagnosis and treatment (part 2) - T.V. Sorokman; O.-M.V. Popeliuk; O.V. Makarova (Zaslavsky O.Yu., 2017)
We searched for published and unpublished research using PubMed as the search engine by the keywords: "Gilbert's syndrome", "clinical manifestation", "diagnosis", "treatment", taking into consideration studies conducted in the last 10 years, citation review of relevant primary and review articles, conference abstracts, personal files, and contact with expert informants. The criterion for the selection of articles for the study was based on their close relevance to the topic, thus, out of 75 analyzed articles, the findings of the researches covered in 28 articles were crucial. Clinical manifestations of Gilbert's syndrome (GS) are possible both in homozygous for UGT1A1, and in heterozygous status. A latent variant of the disease prevails in individuals with heterozygous status. Up to 30 % of homozygous for the defective gene of GS individuals have an asymptomatic course of the disease. Clinical types of GS: dyspeptic - 43.2 %, asthenovegetative - 15.9 %, icteric - 14.8 % and asymptomatic - 26.1 %. Dietary deviations, mental fatigue, stress, trauma, acute infections, including hepatitis, certain medications intake are the triggers for GS. In 86.4 % of children with GS, the pathology of the upper digestive tract was detected: duodenitis - in 58 % of cases, gastritis - in 56.8 %, esophagitis - in 12.5 %, duodenal ulcer - in 2.3 %, in 39.7 % of patients sphincter disorders were registered (duodenogastric and gastroesophageal bile reflux). The GS is characterized by reduced detoxification function of the liver, in particular in 2/3 of patients decreased hepatocyte metabolic activity was observed, the excretory function of liver cell suffers in another half of patients, the biliary tract disorders and increased risk of gallstones formation are described in 88 % of cases. Some patients with GS have certain psychological disorders, including anxiety. Diagnostic criteria for GS: 1. A peculiar pale yellowish discoloration of the skin ("teinte bilieuse"), especially on the face, hands, and feet without a distinct scleral icterus. Sometimes the development of repeatedly intermittent episodes of jaundice with high bilirubinemia (indirect bilirubin) without the evidence of hemolysis (differential diagnostic feature) is observed. 2. A tendency to development of pigmented and vascular nevi and xanthelasma of the eyelids, and hyperpigmentation around the eyes; to bradycardia, hypothermia, migraine, postural, intermittent albuminuria or to alimentary glycosuria. 3. An increased tendency to pigmentation under the influence of light, heat, and also chemical and mechanical stimuli. 4. A neuromuscular hyperexcitability. 5. Increased sensitivity to cold. 6. Dyspeptic complaints (pain, nausea, abdominal bloating, diarrhea or constipation). 7. No signs of increased hemolysis (differential diagnostic feature) with increasing content in, bilirubin (differential diagnostic feature). 8. The majority of patients have normal liver function tests (differential diagnostic feature) also normal bromsulphalein test is also normal (differential diagnostic feature). 9. The biochemical abnormality is not detected by histological methods (differential diagnostic feature) .10. Frequently, a family disease of the liver is observed. The differential diagnosis of GS is conducted with all types of hyperbilirubinemias, hemolytic anemias, congenital hepatic cirrhosis, hepatitis, cholecystopathy, atresia of biliary ducts or the small intestine. Medications are used only in severe hyperbilirubinemias and as concomitant therapy in the presence of symptoms of vitamin deficiencies, violations of a motor-evacuation function of the upper digestive tract in the clinical picture and to prevent complications (cholelithiasis).